Botol Pet, Kemasan Tara-Pangan Pengganti Botol Gelas - Triyanto Hadisoemarto; Wiwik Pudjiastuti (Balai Besar Kimia dan Kemasan, 1998)
Due to is unique characteristics, PET bottle can now be used replacing the glass bottle to pack a variety of foodstuffs, and in certain circumtances can be both reused and recycled.The principal positive features of PET bottle are being reviewed.